Analisis Kelayakan Bisnis Outdoor Plus: Peningkatan Keberlanjutan UMKM Melalui Pendekatan Terpadu (Jurnal Manajemen Kreatif dan Inovasi, 2024)
This research aims to analyze the business feasibility and sustainability impact of "Outdoor Plus" stores as an effort to increase MSMEs. The research methods used are qualitative with data collection through documentation, observation, and interviews. In sustainability analysis, this store emphasizes an integrated approach by utilizing open space to support the visibility of MSMEs products. Loyalty programs, creative marketing strategies, and involvement in local communities are key points in achieving marketing success. Research results show that Outdoor Plus stores have achieved operational efficiency through modern cashier systems, computerized stock management, and online payment integration. Holistic marketing strategies have also succeeded in increasing market share and building strong customer relationships. In addition, effective human resource management, strict legal compliance, and commitment to environmental sustainability have established a strong foundation for sustainable growth. This study is expected to contribute to understanding the potential of sustainable business at the MSMEs level, while providing insights for related stakeholders.